El enfoque territorial en la definición de políticas públicas : el caso del servicio de agua y saneamiento en la Región Metropolitana de Buenos Aires - Rodríguez Tomietto, Alejandra Macarena (2021)
Why is it that belonging to a specific place becomes a development indicator? Can we continue to think about a ?universal and sustainable? service when we refer to an unequal city model which is has been spreading indefinitely? Is it ?sustainable? to work in only certain areas inside an increasingly spread territory?\nReflecting upon the difficulty of accessing to basic services in many cities of Latin America, the Metropolitan Region of Buenos Aires (MRBA) is at a point in which its possibilities of providing universal and sustainable water and sanitation services is not easily achievable. In addition, the political dependence and the jurisdictional fragmentation affect its effectiveness and efficiency (Pírez, 2000) therefore, having an impact on the quality of life of its inhabitants and their development possibilities. This issue shows sciences and inequality policies which reproduce themselves, become naturalised and stronger in certain areas. For this reason, in order to fully understand development as a comprehensive right to have access to opportunities, theoretical and methodological challenges are required in which the focus on the territory, as opposed to traditional planning ideals, will contribute to reinterpreting conflict as an unforseen (or non-authorised) encounter between certain variables which demand a new level of intelligence in their connections. Likewise, this awakening to complexity requires a number of unprecedented institutional movements which entail questioning the established order. This is the reason why some analysed cases such as the creation of the ?Autoridad de Cuenca Matanza Riachuelo? (ACUMAR) and the regionalisation by Hydrologic Basins designed for the licensed company: ?Agua y Saneamientos Argentinos Sociedad Anónima? (AySA S.A) by University of Buenos Aires (UBA) staff members have become two initiaves which have the potential to lead to institutional innovation as long as power relationships are reconsidered. These are some of the reasons why we consider that ?appropriate urban public policies focused on the territory make it possible to address the economic, social and environmental disbalances as a whole?, (Borja, 2013). As a result of all the abovementioned, working on the city once again ?from and towards? the territory in urbanism (and its ability to transfer knowledge) as much as in politics (understood as instrumentation) resignifies the issue of the water and sanitation service in a broad sense. Sustainability, therefore, will depend on its systemic reprogramming and will encourage to produce in a conscious and innovative way in those areas which will not be understood as blind spots anymore but as starting points.